CURRENT TRENDS OF PRESCRIBING PATTERNS OF NSAIDS IN AN ORTHOPAEDIC OPD IN A TEACHING HOSPITAL - SINGH V; YADAV P; DEOLEKAR P (International Journal of Pharma and Bio Sciences, 2014)
There are a variety of NSAIDs available for prescription: traditional non selective (NSAIDs), and the more selective COX-2 inhibitors (Coxibs). The analgesic effects of the different NSAIDs are more or less identical; however, the Coxibs are associated with a lower risk for upper gastrointestinal side effects. Thus, the Coxibs after their introduction become an alternative to traditional NSAIDs in patients exhibiting risk for upper gastrointestinal bleeding However, Post marketing experience unmarked various adverse cardiovascular effects. Evidences of adverse CVS events with the use of COX-2 selective inhibitors have led to their decreased use. The aim of the study was to analyze the prescribing pattern of NSAIDs in patients attending Orthopedics OPD and to correlate the use of selective COX-2 inhibitors and older conventional NSAIDs in practice and also to determine type and frequency of gastro-protective drugs used with NSAIDs.The data was collected from the out-patient case sheets of the patients who were attending Orthopedic out-patient departments (OPDs) for a period of 6 months. NSAIDS were prescribed to 48.19% of the patients. Coxibs and Non Selective NSAIDS accounted for 1.51% and 45.71% respectively. Monotherapy was given to 14.39% and FDCs accounted for 19.29%. Diclofenac 11.77 %, was the commonest prescribed NSAID in monotherapy while Paracetamol 15.12% in FDCs. Maximum number (97.66%) of patients were co- prescribed gastro protective drugs (GPDs) commonest being Rabeprazole 12.19%. The use of Coxibs have decreased to great extent because of reports of cardiovascular adverse effects. The conventional non selective NSAIDs are generally co prescribed with gastro protective drugs.